Coupled CFD and chemical-kinetics simulations of cellulosic-biomass enzymatic hydrolysis: Mathematical-model development and validation. (12th October 2019) - Sitaraman, Hariswaran; Danes, Nicholas; Lischeske, James J.; Stickel, Jonathan J.; Sprague, Michael A.
Highlights: A mathematical model for simulating enzymatic hydrolysis of cellulosic biomass is presented. The model couples transport physics and chemical kinetics. A subcycling method is used to circumvent time scale disparity between transport and chemical kinetics. The reaction and transport model constants are fit to a well-mixed and settled experiment. The model predicts experimental conversion over time for an intermediate mixing scenario. Abstract: Computational simulations of cellulosic-biomass enzymatic hydrolysis using a computational-fluid-dynamics (CFD) model coupled to a chemical-kinetics model are presented in this work. A time-step sub-cycling strategy was used to circumvent large disparities in time scales with respect to transport physics and chemical kinetics. The unknown reaction and transport parameters in the mathematical model were first fit to two canonical experiments: a well-mixed case that was limited by reaction kinetics and a settled-solids case that was limited by transport. The model was then validated against a benchtop experiment for an intermediate-mixing scenario, for which simulation results were in reasonable agreement with experimentally measured cellulose conversions. Settling of cellulose particles and diffusion of enzymes determine overall conversion rates for lower mixing rates, while reaction rates dominate conversion at higher mixing rates for which greater homogenization of substrates is achieved.